2008
DOI: 10.3892/or.19.5.1355
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant chemotherapy with tegafur/uracil administration after transcatheter arterial chemoembolization for advanced hepatocellular carcinoma

Abstract: Abstract. Although transcatheter arterial chemoembolization (TACE) is considered to be an effective treatment for advanced hepatocellular carcinoma (HCC), it is difficult to achieve complete necrosis by TACE alone due to incomplete embolization and tumor angiogenesis. Recent studies have shown that tegafur/uracil (UFT ® ) inhibits tumor angiogenesis in several cancer types. Therefore, this study was conducted to test the efficacy and toxicity of the UFT administration after TACE in advanced HCC. Thirty patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Chemoembolization acts mainly via reducing the local blood flow and currently studies are aiming to decrease the consequences of secretion of proangiogenic factors after this transarterial chemoembolization (1). On the other hand, proangiogenic factors are well known to be stimulated by hypoxia that is caused by the rapid growth of tumor cells and the presence of aberrant blood vessels (2).…”
Section: Introductionmentioning
confidence: 99%
“…Chemoembolization acts mainly via reducing the local blood flow and currently studies are aiming to decrease the consequences of secretion of proangiogenic factors after this transarterial chemoembolization (1). On the other hand, proangiogenic factors are well known to be stimulated by hypoxia that is caused by the rapid growth of tumor cells and the presence of aberrant blood vessels (2).…”
Section: Introductionmentioning
confidence: 99%
“…This finding implicates that an adjuvant treatment to inhibit angiogenesis may be required to make the procedure more effective. A literature search revealed that changes of the anti-angiogenic function after hepatic embolization was only examined by tegafur/uracil (UFT) administration after transcatheter arterial chemoembolization (TACE) in advanced hepatocellular carcinoma (HCC) [32]. Ueda et al found a prolonged time to treatment failure in the group who were treated with UFT compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…tegafur/gimeracil/oteracil potassium, known as Tiji’ao capsule in China) was a novel oral 5-fluoro-2,4 (1 h, 3 h) pyrimidinedione (5-FU) analogue, which contained tegafur and two biochemical modulators for 5-FU. Tegafur was a metabolically activated prodrug of 5-FU, and was effective as adjuvant chemotherapy after TACE [22]. 5-Chloro-2,4-dihydroxypyridine can enhance the pharmacological actions of 5-FU by inhibiting its degradation by dihydropyrimidine dehydrogenase (DPD).…”
Section: Discussionmentioning
confidence: 99%